Study of Some Biochemical Parameters Related to Heart Function in Ascending and Descending Effort - Dhiaa Kasim Al-Khayat; Luay Abed Al-Helaly; Hadeel Tariq Al-Taee (Tikrit Journal of Pure Science)
This research is carried out to study the effect of ascending and descending effort on some biochemical parameters related to heart function which include: Arterial natriuretic hormone, angiotensin II, sodium, potassium, lactate dehydrogenase, creatine kinase, aspartate aminotransferase, adiponectin, lipase, triglycerides, free fatty acid, lipooxygenase and myeloperoxidase . The major samples included (15) of the track and field players participating in Mosul university team of middle-distance runners .